Meaning, Life and Culture In conversation with Anna Wierzbicka - Bromhead, Helen; Ye, Zhengdao (ANU Press, 2020)
This book is dedicated to Anna Wierzbicka, one of the most influential and innovative linguists of her generation. Her work spans a number of disciplines, including anthropology, cultural psychology, cognitive science, philosophy and religious studies, as well as her home base of linguistics. She is best known for the Natural Semantic Metalanguage (NSM) approach to meaning-a versatile tool for exploring 'big questions' concerning the diversity and universals of people's experience in the world. In this volume, Anna Wierzbicka's former students, old and current colleagues, 'kindred spirits' and 'sparring partners' engage with her ideas and diverse body of work. These authors cover topics from the grammar of action verbs to cross-cultural pragmatics, and over 30 languages from around the world are represented. The chapters in Part 1 focus on the NSM approach and cover four themes: lexico-grammatical semantics, cultural keywords, semantics of nouns, and emotion. In Part 2, the contributors connect with a meaning-based approach from their own intellectual perspectives, including syntax, anthropology, cognitive linguistics and sociolinguistics. The deep humanistic perspective, wide-ranging themes and interdisciplinary nature of Wierzbicka's research are reflected in the contributions. The common thread running through all chapters is the primacy of meaning to the understanding of language and culture.